Cathaemasia hians (Digenea, Cathaemasiidae) from Planorbis planorbis (Mollusca, Gastropoda) in Reservoirs of Central Polissya - Zhytova, O.P.; Korol, E.M. (Вестник зоологии, 2012)
The paper presents the description of Cathaemasia hians Rudolphi, 1809 trematode found on the territory of Ukraine in an intermediate host, fresh-water molluscs Planorbis planorbis. We present also a comparison of metrical characters of the studied C. hians cercariae and those described by other researchers.